Influence of sex on development of thrombosis in patients with COVID-19: From the CLOT-COVID study. Issue 213 (May 2022) - Yamashita, Yugo; Yachi, Sen; Takeyama, Makoto; Nishimoto, Yuji; Tsujino, Ichizo; Nakamura, Junichi; Yamamoto, Naoto; Nakata, Hiroko; Ikeda, Satoshi; Umetsu, Michihisa; Aikawa, Shizu; Hayashi, Hiroya; et al.
Abstract: Introduction: There has been limited data on the influence of sex on development of thrombosis in patients with coronavirus disease 2019 (COVID-19). Materials and methods: The CLOT-COVID Study was a retrospective, multicenter cohort study enrolling 2894 consecutive hospitalized patients with COVID-19 among 16 centers in Japan from April 2021 to September 2021. We divided the entire cohort into the men ( N = 1885) and women ( N = 1009) groups. Results: There were no significant differences in D-dimer levels at admission between men and women. Men had more severe status of the COVID-19 at admission compared with women (Mild: 57% versus 66%, Moderate: 34% versus 29%, and Severe: 9.1% versus 5.7%, P < 0.001). Men more often received pharmacological thromboprophylaxis than women (47% versus 35%, P < 0.001). During the hospitalization, men more often developed thrombosis than women (2.5% [95%CI, 1.9–3.3%] versus 0.8% [95%CI, 0.4–1.6%], P = 0.001). Men had numerically higher incidences of thrombosis than women in all subgroups of the worst severity of COVID-19 during the hospitalization (Mild: 0.3% versus 0.0%, Moderate: 1.6% versus 1.0%, and Severe: 11.1% versus 4.3%). Even after adjusting confounders in the multivariable logistic regression model, the excess risk of men relative to women remained significant for thrombosis (adjusted OR, 2.51; 95%CI, 1.16–5.43, P = 0.02). Conclusions: In the current large observational study of patients with COVID-19, men had more severe status of the COVID-19 than women, and the risk of development of thrombosis was higher in men compared with women, which could be helpful in determining the patient-specific optimal management strategies for COVID-19. Highlights: There is limited data on the influence of sex on thrombosis in COVID-19. We investigated clinical characteristics and outcomes between men and women. Men had more severe status of the COVID-19 than women. The risk of development of thrombosis was higher in men compared with women.